Talking Lamb or Deified Sage? - K.V. Kuzmin (Ученые записки Казанского университета: Серия Гуманитарные науки)
The aim of this paper is to find out possible roots of the legend about a prophecy made by a talking lamb in the Egyptian historical tradition. The stories told by Manetho, Chaeremon, and Lysimachus about predictions given to one of the Egyptian kings of the past (that became a source of ancient narratives on the Exodus) have been analyzed. It can be said with a high degree of probability that Amenhotep, a son of Hapu, played the original role of a prophet in this tradition. He was often named by his title Hry-tp. Chaeremon calls him Phritobautes, a clear misinterpretation of the title mentioned. This title had some variations in the demotic language, including such forms as Hr-ib (tp) and Hry-tb. Thus, it was phonetically similar to the word that was a possible source of the demotic word “lamb” (Hyb): the unattested form of Hry-Aba or Hry-Dba, the latter one was used during the Old Kingdom period and could have migrated back to the colloquial language during the rule of the XXVI dynasty when the archaism was spreading. Furthermore, a strange promise to become an uraeus (the king’s serpent) made by the Lamb in “The Oracle of the Lamb” should be mentioned. Considering that uraeus was sometimes called Hry.(t)-tp, it has been suggested that that there’s a trace of the tradition of Amenhotep, a son of Hapu, in this passage. The provided arguments have proved indirectly that the Lamb’s tradition dates back to the epoch of the XXVI dynasty, which was previously substantiated by the recent research.